PENGEMBANGAN MATERI AJAR TEKS BERITA BERBANTUAN APLIKASI GENIALLY PADA SMP KELAS VII SMPN 6 PERCUT SEI TUAN - Adiyat, Muhammad Al; Khairil Ansari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop video-based advertising text teaching materials using the Capcut application for eighth-grade students. This is a research and development (R&D) study that employs the Borg and Gall research procedure, whose stages have been simplified and adapted to the needs and limitations of this study. The stages carried out in this study are: a) Potential and Problems, b) Data Collection, c) Product Design, d) Validation, and e) Revision. The subject of this development research was to obtain valid product results from the three validators: a subject matter expert, a design expert, and an Indonesian language teacher at SMP Negeri 8 Binjai. Data collection techniques included interviews with subject teachers and questionnaires to identify student needs. The results of this study indicate that the product developed—an advertisement text teaching material assisted by Capcut in video format—qualifies as “very good,” with scores of 97.7% from the subject matter expert, 93.6% from the design expert, and 92.5% from the subject teacher, yielding an average score of 94.6%. Thus, it can be concluded that the product developed in this study is suitable for use in instruction.